Escaping orbits in the N‐body ring problem. Issue 1 (4th November 2019) - Navarro, Juan F.; Martínez‐Belda, M. C.
Abstract : The aim of this paper is to start a numerical exploration of the escape in the N ‐body ring problem. When the energy of the orbits is larger than the escape energy, test particles may escape through any of the N openings of the potential well. We have computed the "basins" of escape toward the different directions by means of Poincaré sections. We have also analyzed the proportion of escaping orbits and the direction of escape.